Water harvesting / Mohd Nazri Kamisan … [et al.] - Kamisan, Mohd Nazri; Nik Mustapha, Nik Mohd Zulkifli; Rosian, Hairool Hisham; Abd Aziz, Nurhazirah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Malaysia be blessed with abundant rains, averaging between 2,000 to 3,000mm annual rainfall and we have harnessed its abundant water resources for agriculture and water supply to industries and homes, Rains bring water down to the grounds and its completes the Earth's hydrological cycle. Not all rains fall in water catchments areas and the rainfall distribution is not uniform throughout the year. But consumers still have the convenience of running water at the turn of a tap. Therefore this project was undertaken to reduce; re-use and recycle the water waste in waste-water laboratory. Purpose of the project is to recover and harvest the water-waste usage during the lab session and during washing glassware. Besides, the project objective is to promote eco-friendly environment in our campuses. The raw water was collected from UniKL MICET environmental laboratories. Parameters as Water Quality Index (WQI) being monitored and the result offer quality as tap water yet better as the piping used are PVC.